COMPARISON THE ANTIHYPERTENSIVE AND ANTIOXIDANT POTENTIAL BETWEEN YOUNG MAHOGANY SEEDS EXTRACT WITH MATURE MAHOGANY SEEDS EXTRACT IN RATS WITH HYPERTENSION - I Wayan Putu Sutirta Yasa; Putu Astawa; I Made Jawi (Journal of Global Pharma Technology, 2017)
Mahogany seeds have been used in the community as an antihypertensive and antioxidant. Antihypertensive and antioxidant efficacy of mature mahogany seeds has been proven in hypertensive rats. The purpose of this study was to compare the antihypertensive and antioxidant effect of mature mahogany seeds extract with young mahogany seeds extract. This study is a laboratory experimental design with pre-test and post-test design control groups, with Wistar rats as samples. Thirty rats were divided into 5 groups, each group consist of 6 rats. The control group was given saline every day as a rat model of hypertension. 1-4 treatment groups were each given NaCl and water extract of young mahogany seeds for treatment 1, the ethanol extract of young mahogany seeds as treatment 2, water extract of mature mahogany seeds as treatment 3 and ethanol extract of mature mahogany seeds as treatments 4. Dosages of extract mahogany seeds is 100 mg / head / day for 4 weeks. Before treatment, evaluation of rat blood pressure with special sphygmomanometer was held, and examination of blood MDA as a pre-test data. Further evaluation of MDA and SOD blood pressure are at the end of the study. The data were tested by ANOVA to see the difference between the groups. The results showed a decrease in blood pressure and levels of MDA were significant in all treatments (p <0.05) compared with control as well as an increase in SOD were significantly (p <0.05). The ethanol extract of mature mahogany seeds showed the most excellent antihypertensive and antioxidant properties (p <0.05). From these results, it can be concluded that the ethanol extract of mature mahogany seeds is better than young mahogany seeds extract as an antihypertensive and antioxidant in hypertensive rats.Keywords – antioxidants, hypertensive rats, mature and young mahogany seeds